Towards the molecular diagnosis of bladder and colorectal cancer : Analysis of CD44 exon splicing - Morgan, Sarah Louise (Cranfield University, 2002)
The literature suggests that CD44 has the potential to be used as a non-invasive tumour specific marker for early detection and monitoring. The gene transcript can undergo alternative splicing, leading to the production of a number of isoforms and it has been noted that in neoplastic states this splicing becomes abberant, leading to the production of a number o f variant isoforms. The aim of this study was to analyse CD44 variant expression with the goal o f reaching a platform from which a non- invasive assay for routine clinical use could be produced. In this study, the analysis o f exon junction splicing in bladder cancer has also led to the finding of a tumour specific junction expressed in 64% o f tumours studied. This exon junction (5/11) was found to be the same as that expressed in colorectal cancer. Though mRNA based assays would provide a satisfactory method for exon junction identification, a protein based approach would provide the platform for a more robust assay. Translation of gene expression data led to the design of a short synthetic peptide which overlapped the 5/11 junction, and this was used to produce a novel polyclonal antibody for this transitional epitope. The resulting polyclonal antibody was affinity purified and used in a pilot study of 5/11 expression in bladder and colorectal tumours. In bladder tumours the antibody demonstrated an overall specificity o f 76.5% and an overal sensitivity of 73.1 %, comparable to current commercially available early detection assays. In a Dukes staged colorectal cancer study, no link between stage and grade was noted, but the antibody gave an overall specificity of 76%. Though further analysis is required, it is thought the 5/11 antibody may prove to be a useful tool in the development o f a sensitive and specific assay for the non-invasive detection of bladder and colorectal cancer.